Amniotic membrane graft versus conjunctival autograft for the management of primary pterygium - Ashraf M Gad Elkareem; Asaad Nooreldin (Al-Azhar Assiut Medical Journal, 2018)
Aim To compare amniotic membrane graft versus conjunctival autograft for the management of primary pterygium. Design A prospective, randomized study. Patients and methods Fifty eyes of 50 patients with primary pterygium were prospectively included in this study and were randomized into two groups. Group I included 25 patients who underwent surgical excision and limbal-conjunctival autograft transplantation; group II included 25 patients who underwent surgical excision and human amniotic membrane graft transplantation. Recurrence rate, refractive changes, and complications were evaluated and compared between both groups. Results Recurrence after surgical excision was observed in eight patients with an overall recurrence rate of 16% (8/50) in both groups. The recurrence was slightly higher in the amniotic membrane group, about 20% (five cases) than the conjunctival autograft group which was about 12% (three cases). The recurrence was higher in the first 3 months postoperatively which was about 62% (5/8) in both groups and increased to about 100% (8/8) at 6 months postoperatively. No recurrence was observed in either group after 6 months. Visual acuity improved in 22 and 23 patients while it remained unchanged in three and two patients in group I and group II, respectively. Conclusion Conjunctival autograft should be considered as the first choice for pterygium excision even in recurrent pterygia. Amniotic membrane graft can be considered as a first choice for patients with advanced and diffuse conjunctival involvement or for those who probably will need the conjunctiva for glaucoma-filtering procedure in the future.